2017
DOI: 10.1007/s10517-017-3705-2
|View full text |Cite
|
Sign up to set email alerts
|

Effect of N- and C-Terminal Modifications on Cytotoxic Properties of Antimicrobial Peptide Tachyplesin I

Abstract: We analyze the effects of N-terminal acetylation and C-terminal amidation on the cytotoxic properties of β-hairpin antimicrobial peptide tachyplesin I. MTT-assay showed that modified tachyplesin I exhibited increased cytotoxicity toward both tumor and normal human cells. Hemolytic activity of modified tachyplesin I was also higher than that of the initial molecule. In contrast to non-modified tachyplesin I, the peptide with C- and N-terminal modifications is resistant to proteolytic degradation in fresh human … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0
1

Year Published

2018
2018
2025
2025

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 24 publications
(12 citation statements)
references
References 11 publications
1
10
0
1
Order By: Relevance
“…The C-amidated peptides TI–TIII lysed 66%, 56% and 41% of RBCs at 64 µM respectively (Figure 2b and Table 2). A similar trend but lower hemolytic activity had been reported for TI, TII, and TIII lacking C-terminal amidation at higher peptide concentrations [47], which is known to impact peptide activity [48,49].…”
Section: Resultssupporting
confidence: 73%
“…The C-amidated peptides TI–TIII lysed 66%, 56% and 41% of RBCs at 64 µM respectively (Figure 2b and Table 2). A similar trend but lower hemolytic activity had been reported for TI, TII, and TIII lacking C-terminal amidation at higher peptide concentrations [47], which is known to impact peptide activity [48,49].…”
Section: Resultssupporting
confidence: 73%
“…The peptide DRGN-2 was derived from VK-CATH4.1 by replacing the glycine residue at position 18 of the wild-type sequence with alanine in order to increase the helical propensity of the peptide [38]. In DRGN-3 the N-terminal amine of DRGN-2 is acetylated and its C-terminal carboxy group is amidated in order to reduce susceptibility to proteolytic degradation [39]. These modifications, however, had no significant effect on antimicrobial activity, showing little to no positive contribution from the glycine to alanine substitution nor from capping of the N- and C-termini.…”
Section: Resultsmentioning
confidence: 99%
“… 290 Similarly, Ovchinnikova and co-workers showed that the proteolytic stability of tachyplesin I was enhanced compared to the unmodified AMP following N-acetylation and C-amidation. 291 …”
Section: Chemical Synthesis Of Ampsmentioning
confidence: 99%